2021
DOI: 10.1155/2021/6646804
|View full text |Cite
|
Sign up to set email alerts
|

The 11-Year Prognostic Impact of Chronic Total Occlusion in the Noninfarct-Related Coronary Artery on Patients with Acute Myocardial Infarction

Abstract: Background. The prognostic significance of CTO in the non-IRA in patients with AMI has been under dispute. Relevant long-term follow-up studies are lacking. Hypothesis. CTO in the non-IRA is an independent predictor of poor long-term prognosis in patients with AMI. Methods. We prospectively enrolled 2336 patients with AMI who received emergent percutaneous coronary intervention successfully from January 2006 to May 2011. Our primary endpoints included death from cardiovascular causes, recurrent myocardial infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Therefore, it is possible that patients who present as NSTEMI are found to have an occluded artery actually have a chronically occluded vessel and well-developed collateral flow. Chronic occlusions are relatively common affecting approximately 25% of NSTEMI patients, and, compared to STEMI, NSTEMI patients have more advanced disease affecting mostly 2-or 3-vessels, thus more likely to have a chronic occlusion (An et al 2021). It is important to recall that these NSTEMI patients with an occluded culprit artery may be either an acute Type I MI (elevated troponin plus one additional criteria as described above) and have a suspected infarct-related vessel; as mentioned, NSTEMI patients presenting with an occluded culprit artery are likely to present with a lower left ventricular ejection fraction and demonstrate wall motion abnormalities reflecting the insufficiency of collaterals, and be consistent with Tpye I MI (Bahrmann et al 2011, Khan et al 2017, Karwowski et al 2017b, Hung et al 2018, Hwang et al 2018, Fernando et al 2021.…”
Section: Collateral Blood Flowmentioning
confidence: 99%
“…Therefore, it is possible that patients who present as NSTEMI are found to have an occluded artery actually have a chronically occluded vessel and well-developed collateral flow. Chronic occlusions are relatively common affecting approximately 25% of NSTEMI patients, and, compared to STEMI, NSTEMI patients have more advanced disease affecting mostly 2-or 3-vessels, thus more likely to have a chronic occlusion (An et al 2021). It is important to recall that these NSTEMI patients with an occluded culprit artery may be either an acute Type I MI (elevated troponin plus one additional criteria as described above) and have a suspected infarct-related vessel; as mentioned, NSTEMI patients presenting with an occluded culprit artery are likely to present with a lower left ventricular ejection fraction and demonstrate wall motion abnormalities reflecting the insufficiency of collaterals, and be consistent with Tpye I MI (Bahrmann et al 2011, Khan et al 2017, Karwowski et al 2017b, Hung et al 2018, Hwang et al 2018, Fernando et al 2021.…”
Section: Collateral Blood Flowmentioning
confidence: 99%
“…3,5 MVD with a coexisting CTO lesion in a noninfarct-related artery(non-IRA) is an independent predictor for long-term mortality in AMI patients, 3,4,6 and one study even reported that the presence of CTO alone but not MVD is associated with long-term mortality, 7 indicating the strong association of CTO lesion with cardiac mortality in these patients. 8 However, whether revascularization of CTO lesion in non-IRA will lead to improved clinical outcomes is still controversial. Observational studies [9][10][11][12] and meta-analysis 13,14 favor CTO-PCI; however, the only randomized trial in this field, EXPLORE (Evaluating Xience and Left Ventricular Function in Percutaneous Coronary Intervention on Occlusions After ST-Elevation Myocardial Infarction) trial failed to confirm the benefit of staged PCI of non-IRA CTO in terms of major adverse cardiovascular events (MACEs).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that AMI with MVD was associated with worse clinical outcomes and complete revascularization in these patients will lead to reduced adverse cardiovascular events 3,5 . MVD with a coexisting CTO lesion in a noninfarct‐related artery(non‐IRA) is an independent predictor for long‐term mortality in AMI patients, 3,4,6 and one study even reported that the presence of CTO alone but not MVD is associated with long‐term mortality, 7 indicating the strong association of CTO lesion with cardiac mortality in these patients 8 . However, whether revascularization of CTO lesion in non‐IRA will lead to improved clinical outcomes is still controversial.…”
Section: Introductionmentioning
confidence: 99%